Oferta e distribuição de estágio supervisionado em cursos de odontologia do estado de minas gerais, Brasil - Francisco, Kléryson Martins Soares [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Diniz, Diego Garcia [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2010)
Since 2002, which are in effect the Curriculum Guidelines for National Graduate courses in dentistry. The adequacy of the education needs of the Unified Health System is one of its main goals. As guidance, a way of achieving this goal is through supervised, which are presented as a tool for improving the academic scientific and technical, providing you know the reality of health and society in which to work. This study aims to examine the supply and distribution of supervised in graduate programs in dentistry in the state of Minas Gerais - Brazil. The material for analysis was obtained by sending letters to courses and consulting to its sites on the Internet. Were part of the study, 15 of the 23 courses in the state. It appeared that the load-hours of supervised showed variations between 315 and 975 hours, with only 20% of courses devoted 20% of the total working hours of supervised practice. There was no correlation between the total working hours of the course and working hours of supervised practice. The courses in which the supervised activities were represented only by extra muros showed a lower percentage of working hours in relation to total working hours of the course.
Supply and distribution of supervised in dentistry courses from state ofminas gerais, Brazil
Keywords: Dental; Dentistry; Education; Schools